Chitosan inserts for periodontitis: Influence of drug loading, plasticizer and crosslinking on in vitro metronidazole release - Barat, R.; Srinatha, A.; Pandit, J.K.; Anupurba, S.; Mittal, N. (My University, 2007)
Chitosan based metronidazole (MZ) inserts were fabricated by the casting method and characterized with respect to mass and thickness uniformity, metronidazole loading and in vitro metronidazole release kinetics. The fabricated inserts exhibited satisfactory physical characteristics. The mass of inserts was in the range of 5.63 ± 0.42 to 6.04 ± 0.89 mg. The thickness ranged from 0.46 ± 0.06 to 0.49 ± 0.08 mm. Metronidazole loading was in the range of 0.98 ± 0.09 to 1.07 ± 0.07 mg except for batch CM3 with MZ loading of 2.01 ± 0.08 mg. The inserts exhibited an initial burst release at the end of 24 h, irrespective of the drug to polymer ratio, plasticizer content or cross-linking. However, further drug release was sustained over the next 6 days. Cross-linking with 10% (m/m) of glutaraldehyde inhibited the burst release by ∼30% and increased the mean dissolution time (MDT) from 0.67 to 8.59 days. The decrease in drug release was a result of reduced permeability of chitosan due to cross-linking.
Keywords: Chitosan inserts; Cross-linking; Metronidazole; Periodontitis; Sustained release